Scaffolds of Fish Skin Gelatin from Unicorn Leatherjackets (Aluterus monoceros) Reinforced with Chitosan for Bone Tissue Engineering - Safiah Saah (Science Faculty of Chiang Mai University, 2019)
The aim of this study was to fabricate and characterize scaffolds of fish skin gelatin from unicorn leatherjackets (Aluterus monoceros) reinforced with chitosan for application in bone tissue engineering. The fish gelatin was extracted at 17% yield on the basis of the fish skin, and characterized according to AOAC official methods of analysis. As the fish gelatin exhibited low gel strength, fabrication of chitosan/fish gelatin (CG) scaffolds crosslinked with glutaraldehyde was performed by freeze-drying technique. The superior porous structure, mechanical, and swelling properties of the CG scaffolds in comparison to those of the single component scaffolds were observed. The scaffolds were nontoxic to MC3T3-E1 cells on MTT assay, supported biomineralization, and promoted cell attachment. It can be therefore concluded that the extracted fish gelatin is a feasible biomaterial for scaffold fabrication by reinforcement with chitosan.